(untitled) (Eurasian Journal of Philology Science and Education, 2022)
lists working in various fields of professional activity. The main emphasis is on the need to master the skills of speech culture and speech etiquette perfectly. The experiment made it possible to diagnose the level of language competence of specialists and identify some areas of work to prevent speech disorders in oral spontaneous speech. Speech competence is a component of professional competence of an expert. Despite the existing theoretical and practical work on the studied problem, many of its aspects remain insufficiently developed. Currently, in science there are no unified approaches to solving the problem of speech training of future experts. The authors note communicatively significant violations in the oral spontaneous speech of specialists, which significantly worsen the understanding of speech activity, reveal the features of the mistakes made and give a pragmatic assessment of the linguistic and communicative competencies of a specialist of any level. The relevance of the study is explained by the discrepancy between the degree of proficiency in speech culture and the requirements imposed by modern society on the speech of specialists in their professional activities.